2023
DOI: 10.1038/s41420-023-01370-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting pyroptosis in breast cancer: biological functions and therapeutic potentials on It

Abstract: Pyroptosis is a lytic and inflammatory type of programmed cell death that is mediated by Gasdermin proteins (GSDMs). Attractively, recent evidence indicates that pyroptosis involves in the development of tumors and can serve as a new strategy for cancer treatment. Here, we present a basic knowledge of pyroptosis, and an overview of the expression patterns and roles of GSDMs in breast cancer. In addition, we further summarize the available evidence of pyroptosis in breast cancer progression and give insight int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 143 publications
0
7
0
Order By: Relevance
“…Recent studies have revealed targeting pyroptosis is a promising approach to treat breast cancer (42,43). Evidence are accumulating that by triggering biological process in breast cancer, the tumor microenvironment could be reorganized and thus antitumor immunity could be enhanced (44).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed targeting pyroptosis is a promising approach to treat breast cancer (42,43). Evidence are accumulating that by triggering biological process in breast cancer, the tumor microenvironment could be reorganized and thus antitumor immunity could be enhanced (44).…”
Section: Discussionmentioning
confidence: 99%
“…These pathways play crucial roles in eliminating undesirable or damaged cells from the organism [ 68 , 69 , 70 ]. However, in BC, PCD becomes dysregulated, resulting in the survival and proliferation of cancer cells [ 71 , 72 , 73 ]. The process of PCD can be delineated into three stages: initiation, execution, and degradation and clearance.…”
Section: Stress Signaling and Programmed Cell Death In Bcmentioning
confidence: 99%
“…[8] Currently, a single treatment can hardly fulfill the therapeutic needs of BRCA. Emerging evidences suggest that features based on cell death patterns, such as ferroptosis, [9] pyroptosis, [10] and necroptosis, [11] have significant value in predicting the prognosis, tumor immune microenvironment, and immune therapy response of BRCA patients. Researchers established a cell death index model by comprehensively analyzing diverse cell death patterns, which can accurately predict clinical prognosis and drug sensitivity of triple negative breast cancer (TNBC) after surgery.…”
Section: Introductionmentioning
confidence: 99%